Future trends in security issues in internet and web applications - Pathan, Al-Sakib Khan; Monowar, Muhammad Mostafa (Inderscience Publishers, Switzerland, 2012)
The massive proliferation of Web applications is observed in recent years as the web is embraced by millions of businesses and government sectors as an inexpensive channel to communicate and exchange information with prospects and transactions with customers. Web applications are usually used from a web browser and along with the typical informative site-surfing they cover a range of activities such as e-banking, webmail, online shopping, community websites, blogs, vlogs, network monitoring and bulletin boards while Internet is the implemented networking infrastructure that connects millions of computers together which could be located in different geographic locations.